Anachronismus und Aktualisierung in Ovids ›Metamorphosen‹ Eine Ästhetik uneigentlicher Zeitlichkeit - Geitner, Philipp (Millennium-Studien / Millennium Studies, 2021)
The temporal inconsistencies in Ovid's "Metamorphoses" are just as multifaceted and numerous as the image that has revealed itself in previous interpretations of these text phenomena - often referred to as "anachronisms" - is blurry and diverse. This volume looks at theories of fiction and language to carry out a systematic reevaluation of Ovid's poem that does justice to its ambitious aesthetics both in terms of theory and text analysis.